The Role of Public Sector in Local Economic and Territorial Development Innovation in Central, Eastern and South Eastern Europe - Finka, Maroš; Jaššo, Matej; Husár, Milan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book covers the topic of the role of public sector in the economic and territorial development across several dimensions of spatial planning, e.g. theoretical-methodological (planning cultures, leadership), executive (regional policies, services of general interest), sectoral (energy, tourism, air-quality) or social (social innovation, preservation of cultural heritage). The book delivers up-to date knowledge build on interactions between representatives of different stakeholders of economic and territorial development with the research represented by renowned experts and academicians. This is mirrored in the content of the book, delivering in a consistent form the conceptual explanations combined with the examples of the role of the public sector in fostering the local economies within the frame of spatial planning. The book reflects and transfers the expert knowledge which has been generated during more than a decade of scientific and research activities of Spa-ce.net. Presents a comprehensive view on different aspects of the involvement of public sector in the local and regional spatial development; Includes a combination of macro-regionally specific perspectives with the generalized knowledge; Provides knowledge from various researchers from prestigious European scientific and research teams.
Chapter1: Editorial -- Chapter2: Innovations and changing role of public sector in spatial development strategies - Problems and challenges for local and regional development in Central and Eastern European Countries after 2020 -- Chapter3: Spatial planning policies and the integration models as a mean for a better delivery of services of general interest -- Chapter4: Utilising Endogenous Potentials via Regional Policy-led Development Initiatives in (post-) Industrial Regions of Central Europe -- Chapter5: Energy Sensitive Spatial Planning As A Public Sector Tool Towards Sustainable Economic And Territorial Development -- Chapter6: Determining of land values by spatial location - Supporting public expert committees' in provision of market transparency -- Chapter7: Forest commons as a model for territorial governance -- Chapter8: The role of leadership in public development policies in the contexts of Central European planning culture -- Chapter9: Urban transformation between culturalheritage preservation and local economic development - The public sector between the fronts? -- Chapter10: Social innovations and sustainable economic development: key study Tourism destination management -- Chapter11: Professional capacity building as the public sector intervention towards sustainable economic and territorial development. Key study Knowledge Hubs Network for energy efficiency -- Chapter12: The public in search of identity - new symbolism in urban spaces. A study of central squares of Balkan capitals -- Chapter13: Professional Associations as Public Actors in the Formulation and Implementation of Spatial Development Policies. Key study Monitoring and Evaluation Standard for the Urban Environment of Sofia.
Keywords: Buildings -- Design and construction; Industrial Management; Public administration; Project management; Building Construction and Design; Industrial Management; Public Administration; Project Management